#TITLE_ALTERNATIVE# - WACIKAPUTRA (NIM : 17512012), BINTANG
For the modern society, communication devices are considered one of their most important needs. It proves that the use of communication devices needed to be able to be accessed at any time. Besides that, those devices mentioned has their own limits. Because just like any other electronical products, there comes a time when those devices needed to get charged whe they’re out of battery power. This caused a problem everytime it’s usually being needed the most. Aside from that, it’s safe to say that individual mobility at this modern era has grown a lot compared to around 10 years ago. Seen from the amount of vehicle sales and the amount of choices of public transportations that are growing rapidly. It had caused a huge amount of traffic around the capitol city. It also made the battery issues of the people’s electronic devices become more likely to happen. Especially during traffic. Based on this issue, we have designed a bag, which has a specific use for carrying electronic devices such as laptops and tablets and can be used comfortably and conveniently inside a car while having features which could supports the practical factor by no having to take out the devices from the bag itself.